Relationship between limb and muscle blood flow in man. - Raitakari, M (1996)
1. Since direct measurement of muscle blood flow in humans has been difficult, estimations of muscle flow have been made from measured total limb blood flow using a classic equation that predicts that the fraction of resting blood flow through muscle tissue decreases as total limb flow increases. 2. We used positron emission tomography and 15O-labelled water to directly quantify resting muscle and total limb blood flow in cross-sections of the femoral region in twenty-eight normal subjects (age, 30 +/- 8 years; body mass index, 24.1 +/- 3.3 Kg m-2) under conditions of constant environmental temperature of 22-23 degrees C. 3. Muscle blood flow averaged 3.1 +/- 1.7 ml (100 ml muscle)-1 min-1 (range, 1.1-7.5 ml (100 ml muscle)-1 min-1 and cross-sectional limb blood flow averaged 2.5 +/- 1.1 ml (100 ml limb)-1 min-1) (range, 1.0-4.8 ml (100 ml limb)-1 min-1). A linear relationship was observed between limb and muscle blood flow, and a regression equation was calculated for estimation of muscle blood flow bases on limb flow: muscle flow = (1.41 +/- 0.10) limb flow - (0.43 +/- 0.28). The slope of this equation was significantly greater than 1 (P < 0.001) indicating that the fraction of blood flow perfusing muscle tissue increases as a function of total limb flow. 4. These data provide a new equation for estimation of resting muscle blood flow in normal subjects, and demonstrate that muscle blood flow is the primary determinant of resting blood flow in man.